Geographical distribution of emergency obstetric and neonatal care signal functions in Ethiopian health facilities: 2021-2022 Ethiopian service Provision Assessment (SPA) - Dagne Deresa Dinagde; Habtamu Wana Wada (BMC, 2024)
Abstract Background The maternal mortality ratio in Ethiopia is still high, with an estimate of 412 deaths per 100,000 live births in 2016. Signal functions for emergency obstetric and neonatal care must be accessible and usable in order to successfully prevent maternal deaths. It is an important strategy to reduce maternal and newborn morbidity and mortality in countries with limited resources. Hence, an assessment of the availability of fully functioning EmONC services and their coverage per 500,000 people in Ethiopia is crucial. Methods This study is a retrospective analysis of data from the Ethiopian Service Provision Assessment Survey (ESPA), a national-level survey data source. Data collection for the survey took place from August 11, 2021, to February 4, 2022. For this investigation, 905 healthcare facilities in total were evaluated for the availability of emergency obstetric and new-born care (EmONC) services at all hospitals, selected health centers, and private clinics were evaluated. Descriptive data analysis was done by the using statistical package for social science version 26 (SPSS) to run frequency and cross-tabs. Global Positioning System (GPS) (arc map 10.8) Software was used for spatial distribution in order to locate the physical accessibility of EmONC providing health facilities on flat map surfaces. It was projected based on Ethiopia's geographic coordinate system at Adindan UTM zone 370N. Results Of 905 health facilities, only 442 (49%) could provide fully functioning BEmONC, and 250 (27.6%) health facilities have been providing fully functioning CEmONC. The overall coverage of BEmONC ratios in Ethiopia is 1.5-3.77 per 500,000 population and CEmONC (0.83-2.1) per 500,000 populations. Regions such as Amhara, SNNPR and Addis Ababa had found to have high BEmONC ratio. The geographical distribution of the EmONC showed that the central areas of the country, such as southwest Shewa and east Shewa, the Oromia region, the northern areas of the South Nation, nationalities, and peoples regions (SNNPR), including the Gurage zone and the Wolaita-Soddo zone, and the middle areas in the Amhara region (west Gojjam or around Bahir Dar town), and the southern areas, Debra Tabor and Debre Birhane zones, all had greater access to facilities offering complete EmONC services. Conclusion Comprehensive emergency obstetrics and neonatal care (CEmONC) in Ethiopia met WHO recommendations, despite basic emergency obstetric and neonatal care (BEmONC) falling below those standards in Ethiopia. There are extremely large disparities in the accessibility of both basic and comprehensive emergency obstetrics and neonatal care in Ethiopia. Thus, Strategic planning is needed to improve infrastructures and inputs for EmONC services, particularly in remote areas of the country. Additionally, private facilities ought to place a priority on the provision of these services.